Current hospital policies on breastfeeding: a survey from Italy - Riccardo Davanzo; Laura Travan; Maria Lorella Giannì; Giuseppe Giordano; Silvia Perugi; Mariella Baldassarre; Antonella Soldi; Lorenzo Colombo; Isabella Mondello; Michela Pandullo; Alessia Ferrara; Elena Scarpato; et al. (BMC, 2024)
Abstract Background The availability of an appropriate newborn feeding policy is an essential component of the promotion of breastfeeding in health facilities. The Italian Society of Neonatology (SIN) and the Italian Society of Paediatrics (SIP) have run an online survey among Maternity Hospitals to explore the existing breastfeeding policies and their characteristics. Methods Between February and April 2023, an online survey was carried out among 110 Italian maternity hospitals with a Neonatal Intensive Care Unit (NICU). Results Forty-nine Maternity Hospitals completed the online questionnaire. Twenty out of 49 (40.8%) reported to have a breastfeeding policy. When a policy is available, its quality appears to be suboptimal because of lack of inclusion of a family representative in the policy working group, limited options for translating breastfeeding policy into minority languages, lack of periodic assessment of their implementation. Conclusion Currently, only a limited number of Italian Maternity Hospitals have developed a breastfeeding policy. Additional efforts are needed for their improvement as well as implementation.